Examining the role of emotion regulation in the bidirectional relation between physiological and subjective stress response among daily cigarette smokers. (1st March 2020) - Borges, Allison M.; Yang, Min-Jeong; Farris, Samantha G.; Zvolensky, Michael; Leyro, Teresa M.
Abstract: Cigarette smoking is associated with autonomic dysregulation and altered stress responsivity. There exists a reciprocal relation between subjective and physiological stress reactivity and recovery in smokers. Emotion regulation may impact the extent to which these domains influence each other. The current study examined the moderating role of lack of emotional awareness, lack of emotional clarity, and nonacceptance of emotions, in the relation between heart rate reactivity to, and subjective recovery from, stress, and vice versa. To determine specificity of cross-domain findings, these relations were also examined within domain. Fifty-six daily smokers (46.4% female; M age = 29.33, SD = 11.92) participated in a biological challenge. Heart rate and subjective distress were assessed continuously before, during, and after the challenge. Individual growth curve models revealed that deficits in emotional clarity significantly moderated the effect of heart rate reactivity on subjective recovery. Lack of emotional awareness also moderated the association between subjective reactivity and heart rate recovery. Emotion regulation processes did not affect relations within the same domain, but altered the relation across domains.